Seeing Through the Character's Eyes: Examining Phenomenological Experiences of Perspective-Taking During Reading. Issue 5 (3rd July 2022) - Öncel, Püren; Creer, Sarah D.; Allen, Laura K.
ABSTRACT: Despite substantive work on the cognitive processes underlying comprehension, little research has examined the "phenomenological" nature of reading. We investigated how readers' experiences of visual and verbal thought related to their transportation into the narrative text and whether these were influenced by perspective-taking. Specifically, readers reported the nature of their thoughts while reading and then completed a transportation assessment. Study 1 ( n  = 147) manipulated perspective-taking via explicit instructions, whereas Study 2 ( n  = 200) varied point of view within the text. Additionally, Study 2 examined whether reports varied across descriptive and dialogue text segments. Results suggested that visual and verbal reports were consistently negatively correlated. Further, transportation was positively associated with visual reports and negatively associated with verbal reports. We found no differences in thought reports for dialogue and descriptive text segments or across the perspective-taking manipulations. These findings suggest that phenomenological reading experiences are stable across a variety of reading situations.